The The Impact of Multidimensional Poverty on Pregnant Maternal Health during the Conflict in Sudan - Saleh, Husny Gibreel Musa; Nishad, Muhammed; Othman, Asaad Belal Yahya Mohammed; Babangida, Fahad (JIAN (Jurnal Ilmiah Administrasi Negara), 2025)
The ongoing civil conflict in Sudan has intensified multidimensional poverty, critically impacting maternal health—especially among pregnant women in conflict-affected areas. This paper investigates how the collapse of healthcare infrastructure, displacement, food insecurity, and inadequate sanitation have led to alarming increases in maternal and neonatal mortality. Pregnant women face limited or no access to antenatal care, skilled birth attendants, and emergency obstetric services, compounded by malnutrition, gender-based violence, and psychological trauma. The findings highlight key elements necessary to address the crisis, including enforcing a ceasefire, restoring healthcare services, strengthening emergency medical response, protecting healthcare workers, and establishing safe humanitarian corridors. Policy recommendations emphasize rebuilding health infrastructure, delivering targeted food and nutrition programs, and safeguarding vulnerable populations. A coordinated response involving national actors and international partners is essential to mitigate the ongoing health emergency and support the long-term recovery of Sudan’s maternal healthcare system.